Parenting styles in caregivers of children with Autism Spectrum Disorder and effects of service dogs - Poirier, Margot; Grandgeorge, Marine; François, Nathe; Auffret, Florian; Champagne, Noël; Legrand, Alain; Deschatelets, Catherine; Favier-Hannequin, Nathalie; Tremblay, Aurélie; Kearnan, Fanny; Henry, Séverine; Plusquellec, Pierrich; et al. (Frontiers in Ethology, 2024)
Objective: Parents of children with Autism Spectrum Disorder (ASD) have parenting styles that differ from parents of typically developing children. Integration of a service dog (SD) at home has been demonstrated as having multiple effects within families of children with ASD. Our aims were to investigate if (a) specific parenting styles can be identified during parents’ interactions with their child with ASD using ethological methods, and (b) integration of a SD have an effect on these styles. Methods: Behavioural coding was performed on videos recorded at home by 20 parents of 6-12-years old children with ASD before SD integration. Parents were asked to record themselves and their child while making a puzzle. 14 parents performed a second similar recording 3-6 months after SD integration. Data were analysed using Principal Component Analysis, Hierarchical Cluster Analysis and non-parametric tests. Results: Three parenting styles emerged: Parents Involved in the Task (PIT), Parents Relaxed in the Interaction (PRI), and Parents Disengaged from the Interaction (PDI). PIT were characterised as more controlling and verbally focused on the activity. PRI were less controlling and talk about things other than the activity. The same applied to PDI, except that they were less warm in their interactions. Analysis performed after SD integration revealed that these groups also diverged in the evolution of certain behaviours. Conclusions: This study is the first to demonstrate that behavioural observations can highlight different parenting styles in caregivers of children with ASD, and that the integration of a SD has effects on these styles, with variation according to parents’ style prior to SD integration. Indeed, a decrease in activity control behaviours was observed in parents with an initial profile characterize by higher expression of such behaviours (i.e., PIT), while an increase of those behaviours was observed in parents initially with an initial profile characterize by a weaker expression of such behaviours (i.e., PRI). Interestingly, the last profile characterized by less engagement in the interaction and activity (i.e., PDI) did not seem to show significant changes.